Aspects of DNA interaction with the natural heterocyclic compounds (International Journal of Biology and Chemistry, 2024)
Cancer is now one of the major challenges in the medical world. An unhealthy lifestyle, and abuse or inappropriate use of drugs stimulate this disease. The drug resistance and imperfections of drugs used in cancer therapy have enforced the development of new drugs with therapeutic potential. Despite the introduction of synthetic drugs, the discovery of new drugs with natural origin has increasing attention in the treatment of diseases, recently. As natural compounds show a considerable diversity of chemical structures, they are liable for diverse mechanisms of action and interaction with target molecules. Heterocyclic natural compounds are a substantial part of natural compounds with excellent properties. These compounds possess various interaction modes with DNA. This review focus on the heterocyclic natural compounds with therapeutic potential and their binding mode with DNA.